2006
DOI: 10.1590/s1806-37132006000900003
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose pleural

Abstract: INTRODUÇÃOO comprometimento pleural representa a forma mais freqüente da tuberculose (TB) extrapulmonar. Freqüências variáveis são observadas em diferentes países, de acordo com a prevalência da TB e da sorologia positiva para o vírus da imunodeficiência humana (HIV).(1)A TB pleural pode ser uma manifestação tanto da forma primária da doença (primo-infecção) quanto da reativação de uma infecção latente pelo Mycobacterium tuberculosis. Em ambas a TB pleural está freqüentemente associada à forma pulmonar.(2) Nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Nonetheless, among the patients with nonspecific results, the ELISA IgA fusion protein MT10.3-MPT64 was able to identify all PL-TBs except one. The discovery of specific antibodies to mycobacterial antigens in PL-TB in the absence of histopathological changes could be supportive of the hypothesis that, in some cases, pleural effusion may also be caused by the possible entry of mycobacterial antigens into the pleural space, thereby stimulating the presence of IgA at this site (34). Conversely, only 23.5% (12/51) of the PL-TB patients diagnosed via histopathology had false-negative ELISA IgA fusion protein MT10.3-MPT64 results.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Nonetheless, among the patients with nonspecific results, the ELISA IgA fusion protein MT10.3-MPT64 was able to identify all PL-TBs except one. The discovery of specific antibodies to mycobacterial antigens in PL-TB in the absence of histopathological changes could be supportive of the hypothesis that, in some cases, pleural effusion may also be caused by the possible entry of mycobacterial antigens into the pleural space, thereby stimulating the presence of IgA at this site (34). Conversely, only 23.5% (12/51) of the PL-TB patients diagnosed via histopathology had false-negative ELISA IgA fusion protein MT10.3-MPT64 results.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, it is known that empyema also has its genesis in the rupture of a lung injury, with a significant burden of the M. tuberculosis bacillus in the pleural space representing active disease with pleural contamination by caseous material (34). It is possible that this patient had tuberculous empyema but was wrongly included in the PL-NTB group because all the available resources for TB diagnosis were not utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea was evaluated before and after treatment through a Modified Borg Scale 11 . Both groups received standard TB treatment with rifampin and isoniazid for six months, with the addition of pyrazinamide during the first two months of treatment 3 . Anti-TB drug ingestion was monitored in both groups through daily phone contact.…”
Section: Methodsmentioning
confidence: 99%
“…Pleural TB is the consequence of a delayed-type hypersensitivity reaction in response to the rupture of a subpleural focus of Mycobacterium tuberculosis infection 3 . The main clinical finding is pleural effusion and its diagnosis should be considered in any patient with an exudative effusion 4 .…”
Section: Introductionmentioning
confidence: 99%
“…We do not have the exact prevalence of PT. According to data published by Seiscento et al [4], approximately 8% of new cases are due to PT, which would give an estimate incidence of 5040 cases. In a cross-sectional study involving all TB cases reported to the Brazilian Notifiable Diseases Surveillance System (SINAN) between 2007 and 2011, it was estimated that PT represented 6.9% of TB cases [5].…”
Section: To the Editormentioning
confidence: 98%